The Influence of Group Guidance Services Using Problem Solving Techniques in Determining Career Choices for Class XI Students at SMA Negeri 15 Pekanbaru - Pasaribu, Nidia Friska; Yakub, Elni; Mahdum, Mahdum (FKIP-Universitas Riau, 2024)
The problem of students who are still confused about choosing a career after graduating from school is very influential in students' career development. This research aims to determine the influence of group guidance services with problem solving techniques in determining students' career choices. This research is quantitative research with an experimental method in the form of a one group pretest-posttest design . The subjects of this research were 10 student of class XI students. The data analysis techniques used in this research are descriptive statistics, the Wilcoxon test and the normalized n-gain test . The research results obtained were that there was an increase in students' career choices before and after being given group guidance services using problem solving techniques . Furthermore, this research shows that there are differences in the level of student career choices before and after implementing group guidance services using problem solving techniques . Then it was found that the influence of group guidance services with problem solving techniques on students' career choices was in the medium category. These results indicate that group guidance services using problem solving techniques are influential in determining students' career choices.